Psychological impact of work-integrated learning programmes in Malaysia: The moderating role of self-esteem on relation between self-efficacy and self-confidence [Impacto Psicolgico de Programas de Integracin del Trabajo en Malasia: El Rol Moderador de la Autoestima en la Relacin entre la Autoeficacia y la Autoconfianza] - Jaaffar A.H.; Ibrahim H.I.; Rajadurai J.; Sadiq Sohail M. (Hipatia Press, 2023)
This study further extends a theoretical model of psychological empowerment by investigating the relationships between self-efficacy, self-confidence and self-esteem. A sample of by 383 of Malaysian undergraduates participating in Work Integrated Learning (WIL) programmes across five public universities is used to test the model employing partial-least squares based structural equation modelling. The results have demonstrated that self-efficacy and self-esteem have a positive and significant relationship with self-confidence. This study also confirms the moderating effect of self-esteem on the relationship between self-efficacy and self-confidence. Furthermore, the findings of this study provide insight about psychological attributes of undergraduates participated in WIL programmes. These findings have implications for WIL stakeholders, which are highlighted in the paper. 2019, Hipatia Press. All rights reserved.